Regular expressions for muller context-free languages - Gelle, Kitti; Iván, Szabolcs (Acta Cybernetica, 2017)
Muller context-free languages (MCFLs) are languages of countable words, that is, labeled countable linear orders, generated by Muller context-free grammars. Equivalently, they are the frontier languages of (nondeterministic Muller-)regular languages of infinite trees. In this article we survey the known results regarding MCFLs, and show that a language is an MCFL if and only if it can be generated by a so-called µη-regular expression.